Effect of Indigenous Non-Saccharomyces Yeasts on Lipid Compositions of Maraština Wine - Ana Boban; Urska Vrhovsek; Domenico Masuero; Vesna Milanović; Irena Budić-Leto (Foods)
This study is the first to investigate the impact of indigenous non-Saccharomyces yeasts, including Hypopichia pseudoburtonii, Metschnikowia sinensis/shanxiensis, Metschnikowia chrysoperlae, Metschnikowia pulcherrima, Lachancea thermotolerans, Hanseniaspora uvarum, Hanseniaspora guilliermondii, Hanseniaspora pseudoguilliermondii, Pichia kluyveri, and Starmerella apicola on the lipid composition of sterile Maraština grape juice and wines using the UHPLC-MS/MS method. Yeasts were tested in monoculture and sequential fermentations alongside commercial Saccharomyces cerevisiae. Indigenous non-Saccharomyces yeasts showed the potential to improve fermentation performance and enable the development of new wine styles through the biosynthesis of an unsaturated fatty acid pathway, which was identified as the most significant pathway. In monoculture fermentations, L. thermotolerans, H. uvarum, H. guilliermondii, H. pseudoguilliermondii, and P. kluyveri significantly reduced lignoceric acid, potentially influencing wine aroma through the formation of esters and higher alcohols. Hyp. pseudoburtonii, M. chrysoperlae, M. pulcherrima, P. kluyveri, and S. apicola increased the demand for lipids, such as stearic acid, which may help preserve membrane permeability by integrating into the membrane in response to ethanol shock. The most significant impact on free fatty esters was observed in fermentations with H. pseudoguilliermondii. Furthermore, L. thermotolerans in sequential fermentations significantly reduced arachidic, stearic, and palmitic acid. P. kluyveri reduced the content of erucic and linoleic acid.